1992
DOI: 10.1007/bf00223541
|View full text |Cite
|
Sign up to set email alerts
|

Apparently non-expressed alleles of factor B (BF) code for hypomorphic proteins

Abstract: In three families with an apparent non-expressed factor B (BF) allele (BF*Q0), advanced methods of isoelectric focusing for the determination of BF F subtypes revealed different hypomorphic BF products (BF QL) with functional hemolytic activity expressed by the assumed BF*Q0 allele. A Taq I and a Msp I restriction fragment length polymorphism as well as the Ba fragment of the expression products showed banding patterns for the BF*QL alleles corresponding to BF S types, whereas an altered Bb fragment was seen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Since BF allotypes are demonstrated without bands cathodic to their major band, BF QL products expressed by the other chromosome can be detected [24] if their respective major band is demonstrated more cathodically. Because of its high sensitivity, immunoblotting following IEF methods demonstrates banding intensity relations which are essential for BF allotyping of S, F and FS types, without the clear distinction possible with direct immunofixation.…”
Section: Comparison Of Ief Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Since BF allotypes are demonstrated without bands cathodic to their major band, BF QL products expressed by the other chromosome can be detected [24] if their respective major band is demonstrated more cathodically. Because of its high sensitivity, immunoblotting following IEF methods demonstrates banding intensity relations which are essential for BF allotyping of S, F and FS types, without the clear distinction possible with direct immunofixation.…”
Section: Comparison Of Ief Methodsmentioning
confidence: 98%
“…From this it may be concluded that F types, after treatment with neuraminidase, show no structure, which allows focusing at the isoelectric point ofthe major S band. This makes it possible to use this Ba fragment demonstration when the existence of a Ba S in hypomorphic products of factor B is to be clarified [24]. Because of the great differences in the pattern between the FA subtype, which appears with two intensive bands, and the FB subtype after removal of neuraminic acid residues, these proteins could differ-besides differing in amino acid sequences [40] -in a posttranslational addition of a molecular group.…”
Section: Factor B Structurementioning
confidence: 98%
See 1 more Smart Citation